1991
DOI: 10.1128/mcb.11.1.309
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and activation of epidermal growth factor receptors in cells transformed by the src oncogene.

Abstract: Because functionally significant substrates for the tyrosyl protein kinase activity of pp6)v-slC are likely to include membrane-associated proteins involved in normal growth control, we have tested the hypothesis that pp60v-src could phosphorylate and alter the signaling activity of transmembrane growth factor receptors. We have found that the epidermal growth factor (EGF) receptor becomes constitutively phosphorylated on tyrosine in cells transformed by the src oncogene and in addition displays elevated level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 70 publications
3
44
0
Order By: Relevance
“…For example, EGF/EGFR induces the activation of c-Src in several types of cells (Osherov & Levitzki 1994;Sato et al 1995a;Weernink & Rijksen 1995). On the other hand, over-expression of c-Src results in an augmentation of EGF-responsiveness of cells (Luttrell et al 1988) and EGFR/kinase activity (Wasilenko et al 1991). In addition, it has been shown that c-Src activity is required for the up-regulation of EGFR in lysophosphatidic acid-treated cells (Daub et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For example, EGF/EGFR induces the activation of c-Src in several types of cells (Osherov & Levitzki 1994;Sato et al 1995a;Weernink & Rijksen 1995). On the other hand, over-expression of c-Src results in an augmentation of EGF-responsiveness of cells (Luttrell et al 1988) and EGFR/kinase activity (Wasilenko et al 1991). In addition, it has been shown that c-Src activity is required for the up-regulation of EGFR in lysophosphatidic acid-treated cells (Daub et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these autophosphorylation sites, however, SFK activation can lead to additional tyrosine phosphorylation of EGF-R and to activation of EGFdependent signaling. For example, coexpression of EGF-R and of a temperature-sensitive mutant of v-Src in Rat-1 fibroblasts induces rapid tyrosine phosphorylation of two non-autophosphorylation sites in EGF-R (Wasilenko et al, 1991). Further studies using purified wild-type or kinase-dead EGF-R and c-Src identified three potential sites responsive to c-Src phosphorylation in vitro: Tyr 1148 , Tyr 1173 , and possibly Tyr 703 (Wright et al, 1996).…”
Section: Sfks Modulate Rtks Toomentioning
confidence: 99%
“…There is no indication that calpactin II would become tyrosine phosphorylated in v-src transformed cells (T. Hunter, personal communication), and thus it is not likely a component of the transformation-specific tyrosinephosphorylated 36 kD band. However, it should be kept in mind that calpactin II is an identified substrate for the EGF receptor tyrosine kinase (55) that becomes activated upon v-src transformation (62). The physiological function of calpactins is still unsettled, but they are supposed to be important for cytoskeletal organization.…”
Section: Cytoskeletal Rearrangements May Be Regulated By Polyamine-dementioning
confidence: 99%